Left ventricular hypertrophy and hypertension - Yildiz, Mehmet; Oktay, Ahmet Afşin; Stewart, Merrill H.; Milani, Richard V.; Ventura, Hector O.; Lavie, Carl J. (Progress in cardiovascular diseases, 2020)
Hypertension (HTN) is a major modifiable risk factor for cardiovascular disease (CVD) morbidity and mortality. The left ventricle (LV) is a primary target for HTN end-organ damage. In addition to being a marker of HTN, LV geometrical changes: concentric remodeling, concentric or eccentric LV hypertrophy (LVH) are major independent risk factors for not only CVD morbidity and mortality but also for all-cause mortality and neurological pathologies. Blood pressure control with lifestyle changes and antihypertensive agents has been demonstrated to prevent and regress LVH. Herein, we provide a comprehensive review of literature on the relationship between HTN and LV geometry abnormalities with a focus on diagnosis, prognosis, pathophysiological mechanisms, and treatment approaches.